MEKANISME FISIOLOGIS TUMBUHAN HIPERAKUMULATOR LOGAM BERAT = Heavy Metal Hyperaccumulator Plant Physiology Mechanism - Hidayanti, Nuril (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2013)
One approach to remediate toxic metal pollutants is phytoextraction using hyperaccumulator plants. These plant species are able to accumulate high concentrations of metal ions without suffering fromyield reduction as a result of metal toxicity. Physiological studies showed that metal hyperaccumulation in particular plant species is regulated by multiple pathways and genes controlling metal uptake,accumulation, and tolerance. Currently, research and development on hyperaccumulator plants are progressing in at least seven focus areas: (1) Improving plant root system for higher penetration capacity and more efficient pollutant extraction from heterogeneous contaminated soils, (2) Altering plant’s rhizosphere for secreting various enzymes to enhance extraction, (3) Improving short distance transport systems for nutrients and toxic elements in roots (4) Enhancing mobility of metalsfrom roots up to shoots. (5) Improving long-distance transport of metals, (6) Maximizing capacity of physical sinks such as subcellular vacuoles and epidermal cells and (7) hypertolerance mechanismsto resist the cytotoxic effects of the accumulated metals. Current trends in phytoremediation research are focus at genetic and molecular level. Research objectives in this area include: understanding bio-pathways involved in contaminant degradation and sequestration, identifying specific genes involved in phytoremediation processes, investigating cell signaling pathways that affect genetic expression of plant enzymes, analyzing and identifying root exudates components and chemical fingerprinting to assess phytoremediation effects at specific sites. Keywords: hyperaccumulator, phytoextraction, phytoremediation, heavy metalsAbstrakSalah satu pendekatan untuk memulihkan polutan logam beracun adalah phytoextraction menggunakan tanaman hiperakumulator . Jenis tanaman ini mampu mengakumulasi konsentrasitinggi ion logam tanpa mengalami penurunan hasil akibat keracunan logam. Studi fisiologis menunjukkan bahwa hyperaccumulator logam dalam spesies tanaman tertentu diatur oleh beberapajalur dan gen mengendalikan serapan, akumulasi , dan toleransi logam. Saat ini, penelitian dan pengembangan tanaman hiperakumulator mengalami kemajuan dalam setidaknya tujuh bidangfokus: (1) Meningkatkan sistem perakaran tanaman untuk kapasitas penetrasi yang lebih tinggi dan ekstraksi polutan lebih efisien dari tanah yang terkontaminasi, (2) Mengubah rizosfir tanaman untukmengekstrak berbagai enzim guna meningkatkan ekstraksi, (3) Meningkatkan sistem transportasi jarak pendek untuk nutrisi dan unsur-unsur beracun dalam akar, (4) Meningkatkan mobilitas logamdari akar hingga pucuk, (5) Meningkatkan transportasi jarak jauh dari logam, (6) Memaksimalkan kapasitas tenggelam fisik seperti vakuola subselular, sel-sel epidermis, dan (7) Mekanisme hypertolerance untuk melawan efek sitotoksik dari logam akumulasi . Saat ini kecenderungan dalam penelitian fitoremediasi adalah fokus pada tingkat genetik dan molekuler. Tujuan penelitian di bidangini meliputi: pemahaman bio - jalur yang terlibat dalam degradasi kontaminan dan penyerapan , mengidentifikasi gen tertentu yang terlibat dalam proses fitoremediasi , menyelidiki jalur sinyal selyang mempengaruhi ekspresi genetik dari enzim tanaman , menganalisis dan mengidentifikasi eksudat akar komponen dan sidik jari kimia untuk menilai fitoremediasi efek pada situs tertentuKata Kunci: hiperakumulator, phytoextraction, fitoremediasi, logam berat